Adoption of integrated pest management (IPM) practices by the vegetable growers at sadar upazila under Jhenaidah district: Adoption of IPM practices by the vegetable growers (Journal of the Bangladesh Agricultural University, 2018)
The purposes of the study were to determine the adoption of Integrated Pest Management (IPM) practices by the vegetable growers and to explore the relationships between the adoption of IPM practices in vegetable cultivation and the selected characteristics of the vegetable growers. Data were collected from randomly selected 101 respondents of the three selected villages of ganna union under sadar upazila of Jhenaidah district using interview schedule by the researchers during May to August, 2017. Appropriate scales were used to measure the variables of the study. Correlation test was used to explore the relationships between concerned independent and dependent variables. Majority (72.28%) of the respondents had medium annual income from vegetable cultivation. Majority (58.42%) of the respondents spent moderate time in vegetable field. About one third (36.63%) of the respondents had low knowledge on IPM practices. Majority (58.42%) of the respondents had very low organizational participation and 38.62% of the respondents had low contact with IPM club and FFS. Most (98.02%) of the respondents had low cosmopoliteness. Most (80.20%) of the respondents had low extension media exposure. About half (51.49%) of the respondents had low training exposure related to cultivation practices. Majority (63.37%) of the respondent had unfavorable attitude towards IPM practices. Majority (70.30%) of the respondents had medium level adoption in commonly used IPM practices in vegetable cultivation. Use of pesticides ranked 1st(score 295) as IPM practices compared to other environment friendly practices. Among the fourteen selected characteristics of the respondents, educational qualification, time spent in vegetable field, knowledge on IPM practices in vegetable cultivation, contact with IPM club and FFS, training exposure and attitude towards IPM practices showed positive significant relationships with the adoption of selected IPM practices by the vegetable growers.J. Bangladesh Agril. Univ. 16(3): 366–371, December 2018